Germany's Capacities to Work from Home - Jean-Victor Alipour; Oliver Falck; Simone Schüller (Center for Economic Studies and ifo Institute (CESifo), 2020)
Due to the COVID-19 crisis and the related "social distancing" measures, working from home (WfH) has suddenly become a crucial lever of economic activity. This paper combines survey and administrative data to compute measures for the feasibility of working from home among German employees. Breaking down the data by occupation, region, industry, and employee characteristics, we document considerable variation in the potential to WfH across all dimensions. We find that WfH is feasible for roughly 56 percent of the overall German workforce, while less than half of this potential was exploited in the pre-pandemic economy.
Keywords: D24; J22; J24; O33; R12; 330; COVID-19; working from home; Germany